Poluição do ar e conflitos socioambientais: O caso da fábrica Itaú Contagem Minas Gerais (1975-88) - Renata Cristina Silva (2018)
In the mid-1970s, in the district of Contagem, Minas Gerais, a series of popular protests were organized against the air pollution provoked by the productive activities of the Cimento Portland Itaú Company. The factory, which was settled in the region in the 1940s, was forced since the begging of its foundation, to install anti-pollution equipment in its chimneys to contain the massive dispersion of residues into the atmosphere. The local vicinity, formed by low-income workers, used to complain of cement powder that fell over their residences and, mainly, of respiratory and dermatological diseases that were aggravated by the daily contact with the pollution. In August 1975, the permit of localization and functioning of the factory was suspended by the local executive power due to its inadequacy to the environmental regulations of the district. However, the Decree-Law 1.413/75, issued by the military president Ernesto Geisel, monopolized in the hands of the federal executive power the competence to close factories considered to be of the interest to the National Security. The mayors decision was cancelled and the Itaú Company was reopened, but the problems that had originated the first conflicts continued disturbing the community of the neighbourhoods nearby the factory, which were mobilized in several actions and demanded of the public authority more accurate policies against the pollution of the Itaú factory until the beginning of the 1980s. The socio-environmental conflict related to the pollution involving the Itaú Company is the main object of this research. We seek to understand since when the air pollution became to be questioned by those residents to the point of triggering a political action and a social mobilization. We also analyse the women participation in the movement against pollution and in which way this stimulated their integration into the public arena. We could observe, by means of interviews, clippings of magazines and newspapers, oral testimonies, correspondence from the Department for Political and Social Order (Departamento de Ordem Política e Social or DOPS), among other sources, that the mobilizations organized concerning the pollution issue in Contagem were demands that arose among other innumerable claims against the daily life precariousness of the Brazilian workers in the 1970s and 1980s. Increased pressure for redemocratization contributed so that several unsatisfied social groups manifested their demands in the public arena. Therefore, the socioenvironmental struggles of this period integrated the emergence of new characters of the political action in Brazil that begun to claim better living and working conditions.